Effectiveness of Prone and Orthopneic Positions on Oxygenation and Respiratory Rate in Isolation Ward Patients - Dali, Agus Salim; Sentot Imam Suprapto; Nurwijayanti (Babali Publisher, 2026)
Background: Patients with respiratory disorders in isolation wards frequently experience hypoxia, and body positioning is a non-invasive strategy to improve oxygenation. Although prone and orthopneic positions are widely applied, comparative evidence regarding their effectiveness on oxygen saturation and respiratory rate in isolation ward patients remains limited. This study aimed to compare the effects of prone and orthopneic positions on oxygen saturation and respiratory rate among patients in isolation wards.Methods: A quasi-experimental study with a pre–post test and control group design was conducted. Sixty-six eligible patients were recruited using purposive sampling based on predefined inclusion criteria, then randomly allocated into three groups using simple randomization: prone position (n=22), orthopneic position (n=22), and head-up control position (n=22). Oxygen saturation and respiratory rate were measured at baseline, 30 minutes, and 60 minutes after the intervention, and data were analyzed using Repeated Measures ANOVA and One-Way ANOVA for between-group comparisons.Results: Both prone and orthopneic positions significantly increased oxygen saturation and reduced respiratory rate compared with the control group (p < 0.05). The improvements were clinically meaningful in both intervention groups, with greater enhancement of oxygen saturation observed in the orthopneic position. Minimal physiological changes were found in the control group.Conclusion: Prone and orthopneic positions are effective non-invasive interventions for improving oxygenation and reducing respiratory rate in patients with respiratory disorders in isolation wards, with the orthopneic position demonstrating a marginally superior effect on oxygen saturation. Future studies are recommended to evaluate the long-term effects, optimal duration, and patient comfort associated with each positioning strategy across different respiratory conditions.